Analisis Kegagalan Pipa Elbow Superheater 90° Terhadap Perlakuan Bending Menggunakan Hydraulic Pipa Bender - Sampurno, Rachmat Dwi; Tafrant, Dodi; Putri, Fenoria; Hendradinata, Hendradinata; Arnoldi, Dwi; Ramadhan, Surya (Universitas Muria Kudus, 2025)
Steam power plants are the most widely used power plants. The steam produced will be channeled using a superheater pipe. The component that often fails is the superheater elbow pipe. The method used is purposive sampling. The test method used is metallographic testing where the test is based on ASTM. For the results of reading the microstructure content, the percentage of the microstructure phase of the sample tested was factory factory elbow superheater pipe with a percentage of 53.50% pearlite and 27.50% ferrite, the flexible superheater elbow pipe sample contained 43.00% pearlite and 36% ferrite. . 00%, the leaking superheater elbow pipe sample contained 37.50% pearlite and 43.00% ferrite. So the conclusion is that the superheater elbow pipe which has high hardness and good pearlite and ferrite content is found in the factory ebow superheater pipe sample, the manual bending elbow superheater pipe experienced a reduction in the pearlite phase and the addition of a ferrite phase, so it can be concluded that this sample experienced a reduction in resistance and hardness, The Leaking superheater elbow pipe sample has high hardness due to the heat treatment process and a martensite phase appears due to heating, while the percentage of pearlite decreases and ferrite increases, and if there is more ferrite in the material, the pressure in the pipe will be decreased.Steam power plants are the most widely used power plants. The steam produced will be channeled using a superheater pipe. The component that often fails is the superheater elbow pipe. The method used is purposive sampling. The test method used is metallographic testing where the test is based on ASTM. For the results of reading the microstructure content, the percentage of the microstructure phase of the sample tested was factory factory elbow superheater pipe with a percentage of 53.50% pearlite and 27.50% ferrite, the flexible superheater elbow pipe sample contained 43.00% pearlite and 36% ferrite. . 00%, the leaking superheater elbow pipe sample contained 37.50% pearlite and 43.00% ferrite. So the conclusion is that the superheater elbow pipe which has high hardness and good pearlite and ferrite content is found in the factory ebow superheater pipe sample, the manual bending elbow superheater pipe experienced a reduction in the pearlite phase and the addition of a ferrite phase, so it can be concluded that this sample experienced a reduction in resistance and hardness, The Leaking superheater elbow pipe sample has high hardness due to the heat treatment process and a martensite phase appears due to heating, while the percentage of pearlite decreases and ferrite increases, and if there is more ferrite in the material, the pressure in the pipe will be decreased.